Birth Ball terhadap Lama Kala I Fase Aktif pada Ibu Bersalin - Linawati, Linawati; Rahmita, Hirza; Aifa, Wira Ekdeni; Meri, Dilgu (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of birth ball use on the duration of the first active phase of labor in laboring women in the Lubuk Kandis Community Health Center (Puskesmas) in Indragiri Hulu Regency. The method used was a quantitative study with a quasi-experimental, posttest-only control-group design. The results showed a difference in the duration of the first active phase between the intervention and control groups (p = 0.003; p < 0.05), indicating that birth ball use significantly shortened the first active phase in laboring women. The conclusion, birth ball use is effective in accelerating the progress of the first active phase of labor and can be used as a safe and beneficial non-pharmacological intervention in labor care.   Keywords: Birth Ball, Laboring Women, First Active Phase